2022
DOI: 10.1103/physrevd.106.082005
|View full text |Cite
|
Sign up to set email alerts
|

Targeted search for the kinematic dipole of the gravitational-wave background

Abstract: There is growing interest in using current and future gravitational-wave interferometers to search for anisotropies in the gravitational-wave background. One guaranteed anisotropic signal is the kinematic dipole induced by our peculiar motion with respect to the cosmic rest frame, as measured in other full-sky observables such as the cosmic microwave background. Our prior knowledge of the amplitude and direction of this dipole is not explicitly accounted for in existing searches by LIGO/Virgo/KAGRA but could p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…A detection of pixel-scale anisotropy could provide the first indication of a single inspiraling SMBHB system which could then be subjected to targeted followup using both PTA GW and electromagnetic observatories. A detection of large scale anisotropy could indicate an over-density of SMBHB systems in a cluster environment, or might point to an extrinsic effect (Chung et al 2022), such as the kinematic dipole observed with the cosmic microwave background (Planck Collaboration et al 2020) and predicted to be detectable with a GWB (Bertacca et al 2020;Chung et al 2022;Cusin & Tasinato 2022;Valbusa Dall'Armi et al 2022). If we live in a Universe where both astrophysical (e.g., from SMBHBs) and cosmological (e.g., from cosmic strings) GWBs are present, we can leverage our knowledge of the different expected spatial (and spectral) distribution of these processes to disentangle them in the PTA datasets (Ungarelli & Vecchio 2001;Mandic et al 2012;Parida et al 2016;Biscoveanu et al 2020;Martinovic et al 2021;Suresh et al 2021;Kaiser et al 2022).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…A detection of pixel-scale anisotropy could provide the first indication of a single inspiraling SMBHB system which could then be subjected to targeted followup using both PTA GW and electromagnetic observatories. A detection of large scale anisotropy could indicate an over-density of SMBHB systems in a cluster environment, or might point to an extrinsic effect (Chung et al 2022), such as the kinematic dipole observed with the cosmic microwave background (Planck Collaboration et al 2020) and predicted to be detectable with a GWB (Bertacca et al 2020;Chung et al 2022;Cusin & Tasinato 2022;Valbusa Dall'Armi et al 2022). If we live in a Universe where both astrophysical (e.g., from SMBHBs) and cosmological (e.g., from cosmic strings) GWBs are present, we can leverage our knowledge of the different expected spatial (and spectral) distribution of these processes to disentangle them in the PTA datasets (Ungarelli & Vecchio 2001;Mandic et al 2012;Parida et al 2016;Biscoveanu et al 2020;Martinovic et al 2021;Suresh et al 2021;Kaiser et al 2022).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…A detection of pixel-scale anisotropy could provide the first indication of a single inspiraling SMBHB system that could then be subjected to targeted follow-up using both PTA GW and electromagnetic observatories. A detection of large-scale anisotropy could indicate an overdensity of SMBHB systems in a cluster environment, or might point to an extrinsic effect (Chung et al 2022), such as the kinematic dipole observed with the cosmic microwave background (Planck Collaboration et al 2020) and predicted to be detectable with a GWB (Bertacca et al 2020;Chung et al 2022;Cusin & Tasinato 2022;Valbusa Dall'Armi et al 2022). If we live in a Universe where both astrophysical (e.g., from SMBHBs) and cosmological (e.g., from cosmic strings) GWBs are present, we can leverage our knowledge of the different expected spatial (and spectral) distribution of these processes to disentangle them in the PTA data sets (Ungarelli & Vecchio 2001;Mandic et al 2012;Parida et al 2016;Biscoveanu et al 2020;Martinovic et al 2021;Suresh et al 2021;Kaiser et al 2022).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…But, as for the CMB, it is potentially well larger than intrinsic cosmological anisotropies (see, e.g., the studies [34][35][36][37][38][39][40]). Kinematic anisotropies is a topic of active research in the context of GW interferometers [23,[41][42][43][44][45]. It is then worth asking what information we can obtain from a possible future detection of kinematic anisotropies with PTA experiments.…”
Section: Introductionmentioning
confidence: 99%